Elemental compositions of Nile crocodile tissues (Crocodylus niloticus) from the Kruger National Park - Van der Westhuizen, Donné (North-West University (South Africa), 2019)
A SANParks programme assessed the health of wild Nile crocodiles in the Kruger National Park (KNP) during 2010, with appropriate permits and ethical clearance. Samples were collected from sixteen shot crocodiles (eight males and eight females) from the Sabie, Olifants, Crocodile, Levuvhu, Shingwedzi, Nwaswitsontso, and Letaba rivers, collected by SANParks staff. The samples were collected to obtain more information on the biology, pathology, and ecotoxicology of wild crocodiles, based on the 2008/09 mass crocodile mortality events in the Olifants and Letaba rivers. The aim of the current study was to provide an assessment of the elemental composition of legacy samples already collected and analysed. To achieve this aim, the elemental composition of five different tissues of 16 Nile crocodiles (Crocodylus niloticus) collected in the Kruger National Park was measured and assessed. Additionally, it was determined which tissue(s) would be representative for possible future biopsies from catch and release crocodiles to assess any changes in environmental concentrations. Muscle (from the tail) and tail fat tissue is relatively easily assessable after live capture, while liver, kidney and abdominal fat are more difficult to sample. Most of the elements that were not statistically different between muscle and the other tissues were with kidney (31 elements) and liver (34 elements) tissues. Muscle tissue had no differences with 21 elements for both tail fat and abdominal fat. Kidney and liver shared 38 elements with no significant different concentrations, but only 10 and 16 with abdominal fat and tail fat, respectively. Only three elements were comparable between liver and tail fat, but had no significant different concentrations for 16 elements with abdominal fat. Tail fat and abdominal fat, on the other hand, had no differences whatsoever for any of the 47 elements thus compared. There were surprisingly little direct associations of concentrations between mass and length. This may be due to differences in individual life histories of long-lived animals and feeding preferences. It is clear that there is little pattern of prediction or consistency of elemental concentrations between tissues, except between the two fatty tissues, and kidney and liver to some extent. To a lesser extent, muscle and liver, and muscle and kidney had corresponding concentrations. These tissues may therefore be useful when taking biopsies from live animals to determine pollutant loads in the crocodiles. There were few patterns to discern, but mass, length, and sex did not discriminate between elemental concentrations with any confidence in any tissue. Due to the large variations in concentrations, proper scientific studies using live-captured animals would need a balanced sampling design. The numbers of individuals needed for such a scientific study for the targeted elements and organs can be calculated from my data. However, it seems that for regular and general surveys, the capture and biopsy of fewer animals with less consideration for mass, length and sex, may be appropriate. This investigation provides the largest elemental concentration dataset and baseline for any African crocodile. The data and interpretations will assist in monitoring changes and comparisons with other regions and contribute to a better understanding of the biology, ecology, and threats faced by these apex predators, the largest in Africa.
MSc (Zoology), North-West University, Potchefstroom Campus
Keywords: Nile crocodile; Crocodylus niloticus; Kruger National Park; Elemental compositions; Biopsies; Elemental concentrations